Assignment of near-edge x-ray absorption fine structure spectra of metalloporphyrins by means of time-dependent density-functional calculations - Schmidt, Norman Anja; Fink, Rainer; Hieringer, Wolfgang (Journal of Chemical Physics, 2010)
The C 1s and N 1s near-edge x-ray absorption fine structure (NEXAFS) spectra of three prototype tetraphenyl porphyrin (TPP) molecules are discussed in the framework of a combined experimental and theoretical study. We employ time-dependent density-functional theory (TDDFT) to compute the NEXAFS spectra of the open- and closed-shell metalloporphyrins CoTPP and ZnTPP as well as the free-base 2HTPP in realistic nonplanar conformations. Using Becke's well-known half-and-half hybrid functional, the computed core excitation spectra are mostly in good agreement with the experimental data in the low-energy region below the appropriate ionization threshold. To make these calculations feasible, we apply a new, simple scheme based on TDDFT using a modified single-particle input spectrum. This scheme is very easy to implement in standard codes and allows one to compute core excitation spectra at a similar cost as ordinary UV/vis spectra even for larger molecules. We employ these calculations for a detailed assignment of the NEXAFS spectra including subtle shifts in certain peaks of the N 1s spectra, which depend on the central coordination of the TPP ligand. We furthermore assign the observed NEXAFS resonances to the individual molecular subunits of the investigated TPP molecules. © 2010 American Institute of Physics.

Electronic Structure of Molecular Magnets - Schmidt, Norman Anja; Graf-Zeiler, Birgit; Scheurer, Andreas; Prakash, Raju; Saalfrank, Rolf; Goering, E.; Fink, Rainer (BESSY Annual Reports 2006, 2006)

Electron-vibron coupling in halogenated acenaphthenequinone upon O K-edge soft x-ray absorption - Schmidt, Norman Anja; Clark, Timothy; Urquhart, Stephen G.; Fink, Rainer (Journal of Chemical Physics, 2011)
We present high resolution oxygen K near-edge x-ray absorption spectra of the acenaphthenequinone (ANQ) derivative 3,8-dibromo-5,6-dichloro-ANQ (Br Cl-ANQ). The spectral features exhibit an almost identical vibronic fine structure compared to that shown by ANQ. The unequal distances of the vibronic levels as derived from the least-squares fit analysis of the vibronic progressions allows us to determine the anharmonicity of the excited state potentials involved. We conclude that a single vibrational progression couples to the resonant excitation of O 1s core electrons preferentially. Comparison of the two ANQ derivatives gives a clear indication that the vibronic mode corresponds to a C=O stretching mode, rather than coupling to a C-H mode as suggested previously. These conclusions are supported by density functional theory calculations. © 2011 American Institute of Physics.

Matrix effects in the C 1s photoabsorption spectra of condensed naphthalene - Schmidt, Norman Anja; Wenzel, Jan; Dreuw, Andreas; Fink, Rainer; Hieringer, Wolfgang (Journal of Chemical Physics, 2016)
High-resolution C 1s near-edge x-ray absorption fine structure (NEXAFS) spectra of naphthalene are investigated. By comparing the spectral signatures of condensed naphthalene molecules with those of naphthalene in the gas phase, we are able to unambiguously identify spectral features which are affected by the intermolecular interactions in the condensed phase. With the help of calculations using time-dependent density-functional theory and the second-order algebraic-diagrammatic construction scheme for the polarization propagator, resonances in the relevant energy range can be assigned to valence and Rydberg-like excitations. Thus, we obtain a more detailed identification of NEXAFS resonances beyond the present literature.
EAM Import::2019-03-12

Microspectroscopic analysis of the X-ray-induced photoreduction in Fe-and Mn-containing SMMs - Schmidt, Norman Anja; Scheurer, Andreas; Sperner, Stefan; Fink, Rainer (Zeitschrift für Naturforschung Section B-A Journal of Chemical Sciences, 2010)
Scanning transmission X-ray microspectroscopy (STXM) and L-edge near-edge X-ray absorption fine structure (NEXAFS) spectroscopy have been applied to study the valence states of metal ions in various Fe-and Mn-containing single-molecule magnet materials, in particular the ligand-stabilized metal complexes NaFe (so-called "ferric wheel"), Fe (so-called "ferric star") and Mn (so-called "manganese wheel"). We compare dose-dependent L-edge absorption spectra with the results of theoretical studies of the involved metal ions to conclude on the change in oxidation state upon increasing the X-ray dose. It is found that even low-intensity irradiation induces the reduction of the weakly interacting metal ions, and that the soft X-ray-induced photoreduction is less pronounced in microcrystalline films. © 2010 Verlag der Zeitschrift für Naturforschung, Tübingen.
Keywords: Single-molecule Magnet (SMM); X-Ray Absorption; X-Ray Microspectroscopy; STXM; Photoreduction

Structure, morphology and interface properties of ultrathin SnTTBPP(OH)2-films adsorbed on Ag(100) - Schmidt, Norman Anja; Hub, Christian; Gnichwitz, Jan-Frederik; Hieringer, Wolfgang; Hirsch, Andreas; Fink, Rainer (Physical Chemistry Chemical Physics, 2011)
The molecular interaction of dihydroxo[5,10,15,20-tetrakis(4-tert-butyl- phenyl)porphyrinato]-tin(iv) (SnTTBPP(OH)), the structural order and growth of ultrathin films on Ag(100) have been studied by means of low-energy electron diffraction (LEED) and synchrotron based photoelectron spectroscopy, i.e., X-ray photoemission (XPS) and near-edge X-ray absorption fine structure (NEXAFS/XANES) spectroscopy. For the first time, monolayer adsorption of a metalloporphyrin with octahedral coordination of the metal center by two additional axial hydroxo ligands is investigated in a multi-technique study. The delicate balance of molecule-substrate interactions and intermolecular interactions leads to the formation of a densely-packed organic monolayer which is commensurate with the Ag(100) substrate. From NEXAFS linear dichroism an almost coplanar orientation of the porphyrin system is derived. XPS and NEXAFS clearly indicate that the axial hydroxo ligands are cleaved in monolayer films, i.e., upon adsorption to the Ag substrate. With increasing film thickness orientational order gets lost and leads to polycrystalline growth for thicker films as confirmed by scanning X-ray transmission microscopy (STXM). © 2011 the Owner Societies.